2009
DOI: 10.1890/08-0838.1
|View full text |Cite
|
Sign up to set email alerts
|

Friendly competition: evidence for a dilution effect among competitors in a planktonic host–parasite system

Abstract: The "dilution effect" concept in disease ecology offers the intriguing possibility that clever manipulation of less competent hosts could reduce disease prevalence in populations of more competent hosts. The basic concept is straightforward: host species vary in suitability (competence) for parasites, and disease transmission decreases when there are more incompetent hosts interacting with vectors or removing free-living stages of a parasite. However, host species also often interact with each other in other e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 69 publications
2
101
1
Order By: Relevance
“…The dilution effect could reduce an individual's risk of predation in group-forming animals (Hamilton, 1971;Hall et al, 2009;Marcoux, 2011;Rodgers et al, 2011). Our reOur reOur results suggested that colonies of R. chinensis experienced the same dilution effect as described previously in R. speratus .…”
Section: Discussionsupporting
confidence: 72%
“…The dilution effect could reduce an individual's risk of predation in group-forming animals (Hamilton, 1971;Hall et al, 2009;Marcoux, 2011;Rodgers et al, 2011). Our reOur reOur results suggested that colonies of R. chinensis experienced the same dilution effect as described previously in R. speratus .…”
Section: Discussionsupporting
confidence: 72%
“…Three lines of evidence suggest that this decline was due, at least in part, to food limitation in both treatments. First, densities of the competitor D. pulicaria, which completely resists Metschnikowia infection (Hall et al 2009c), increased in both treatments over time ( Fig. 4d; time F 7,42 = 24.7, P \ 0.0001).…”
Section: Resultsmentioning
confidence: 95%
“…Then, with more finely scaled time series data, we first calculated cross-correlations between total host density and infection prevalence at different lags, ranging from one to four sampling visits (i.e., a lag of four visits means that infection prevalence now correlates with host density four sampling dates (12-16 days) from this time onwards). Multivariate autoregressive (MAR) models were used to quantify interaction strengths between infected hosts (I) and two stage classes of uninfected hosts, namely, adults (A U ) and juveniles (J U ) [following Ives et al (2003) and especially Hall et al (2009c); see ESM for details of this analysis].…”
Section: Field Datamentioning
confidence: 99%
“…A negative correlation between community diversity and parasite incidence is therefore expected. However, the net benefit of the dilution effect for the most sensitive host species depends on the trade-off between lower parasite incidence and higher interspecific competition Hall et al 2009).…”
Section: Host Assemblages: From Theory To Incomplete Empirical Studiesmentioning
confidence: 99%